Sealant and Permanent First Molars Status among Grade 3 Students in Nakhon Sawan: Academic Year 2007 - Poehom, Kanokporn (Journal of Health Science of Thailand, 2018)
The objective of this retrospective observational study was to compare the status of permanent first molars among grade 3 students who had and did not have permanent first molars sealed when they were in grade 1 in academic year 2005. Secondary data was drawn from Yim Sodsai project. The total number of 1,604 samples whose four permanent first molars were fully erupted, caries free, no previous sealed and needed to be sealed were divided into sealed and unsealed groups by using the criteria of having sealant in permanent first molars and primary caries status. Descriptive statistics, chi square and independent t-test were used to analyze the data. The result of this study showed that permanent first molars caries free rate of sealed and unsealed group were 84.1 and 80.6 percent respectively, yet, sealed status was not statistically associated with caries free status (p>0.05). The average number of decayed, missed and filled teeth (DMFT), decayed teeth (DT), missed (MT) and filled teeth (FT) of the sealed group were 0.27 (SD 0.73), 0.20 (SD 0.63), 0 and 0.07 (SD 0.37) respectively. DMFT, DT, MT and FT of the unsealed group were 0.32 (SD 0.73), 0.27 (SD 0.63), 0.003 (SD 0.05) and 0.04 (SD 0.27) respectively. The DT of the sealed group (0.20, 0.63) was statistically different from the unsealed group (0.27, SD 0.63) (pvalue 0.044). Among the students who had average number of decayed, missed and filled primary teeth more than six (dmft >6), those whose permanent first molars were sealed were likely to be caries free in permanent first molars 1.77 times than those who were not (p-value 0.004).